The impact of organized breast assessment on survival by stage for screened women diagnosed with invasive breast cancer. (October 2018) - Smith, Courtney R.; Chiarelli, Anna M.; Holloway, Claire MB.; Mirea, Lucia; O'Malley, Frances P.; Blackmore, Kristina M.; Pandya, Anjali; Majpruz, Vicky; Harris, Cathy Paroschy; Hendry, Ashley; Hey, Amanda; Kornecki, Anat; et al.
Abstract: Purpose: Since 1998, the Ontario Breast Screening Program (OBSP) has offered organized assessment through Breast Assessment Centres (BAC). This study compares survival between screened women diagnosed with breast cancer who have undergone assessment through a BAC and usual care (UC). Methods: A retrospective design identified two concurrent cohorts of women aged 50 to 69 within the OBSP diagnosed with screen-detected invasive breast cancer at a BAC (n = 2010) and UC (n = 1844) between 2002 and 2010 and followed until 2016. Demographic and assessment characteristics were obtained from the OBSP. Abstraction of medical charts provided prognostic and treatment data. Death data were assessed from the Registered Person's Database and the Ontario Registrar General All-Cause Mortality File. Multivariable Cox proportional hazards models compared overall survival by assessment type (BAC/UC), stratified by stage. Results: There were 505 deaths during the study (BAC = 239; UC = 266). Among women with stage I screen-detected breast cancer, those diagnosed through a BAC had 31% reduced risk of all-cause mortality (HR = 0.69, 95% CI = 0.53–0.90) compared to UC. Diagnosis within 7 weeks of an abnormal mammogram reduced the hazard of death from all causes by 34% among all women with stage I breast cancers (HR = 0.66, 95% CI = 0.47–0.91), and was more likely in BAC (79.7%) than UC (66.9%). Conclusion: The significant improvement in overall survival for women with stage I screen-detected invasive breast cancer assessed through BACs further supports the recommendation that women with abnormal mammograms should be managed through organized assessment. Highlights: Diagnosis was more likely within 7 weeks through organized breast assessment. Diagnosis within 7 weeks reduced all-cause mortality for stage I patients. Mortality reduced for stage I patients diagnosed through organized assessment.